Regenerating the Injured Spinal Cord at the Chronic Phase by Engineered iPSCs‐Derived 3D Neuronal Networks. Issue 11 (7th February 2022) - Wertheim, Lior; Edri, Reuven; Goldshmit, Yona; Kagan, Tomer; Noor, Nadav; Ruban, Angela; Shapira, Assaf; Gat‐Viks, Irit; Assaf, Yaniv; Dvir, Tal
Abstract: Cell therapy using induced pluripotent stem cell‐derived neurons is considered a promising approach to regenerate the injured spinal cord (SC). However, the scar formed at the chronic phase is not a permissive microenvironment for cell or biomaterial engraftment or for tissue assembly. Engineering of a functional human neuronal network is now reported by mimicking the embryonic development of the SC in a 3D dynamic biomaterial‐based microenvironment. Throughout the in vitro cultivation stage, the system's components have a synergistic effect, providing appropriate cues for SC neurogenesis. While the initial biomaterial supported efficient cell differentiation in 3D, the cells remodeled it to provide an inductive microenvironment for the assembly of functional SC implants. The engineered tissues are characterized for morphology and function, and their therapeutic potential is investigated, revealing improved structural and functional outcomes after acute and chronic SC injuries. Such technology is envisioned to be translated to the clinic to rewire human injured SC. Abstract : In a novel approach to regenerate the injured spinal cord (SC) at the chronic stage, induced pluripotent stem cells are encapsulated in a hydrogel to potentially form patient‐specific implants. The cells are differentiated to SC motor neurons and form 3D neuronal networks that bridge over the injured axons. The implants reduce inflammation, enhance nerve regeneration, and significantly improve locomotion.